(untitled) (Papeles, 2016)
During the last decades, the discussion of the writing process, in the academic field, has focused on the study of academic practices, didactic situations, sociocultural factors and students’ discursive deficit. In contrast, this article aims to contribute to this reflection from the search and controversy of common knowledge (social representations) in relation to writing inside the research formation process of students and teachers, in this particular case, in the execution of degree projects in Bachelor Degree in Spanish Language and English at Antonio Nariño University. Such inquiry recognizes that heterogeneity of academic cultures is also configured from the participants’ knowledge and beliefs, allowing the identification of correspondences and differences between common knowledge and scientific thinking about writing inside the research formation process.